Women, Gender and Daesh Radicalisation - Elizabeth Pearson (The RUSI Journal, 2017)
In this article, Elizabeth Pearson and Emily Winterbotham explore the role of gender in radicalisation to Daesh (also known as the Islamic State of Iraq and Syria, ISIS). They discuss possible factors in female radicalisation, and how radicalisation differs between men and women. They find that the gender of the recruit affects the enabling factors, mechanisms and locations relating to radicalisation. The article challenges assertions that the recruitment of young men and women to Daesh follows identical patterns, as well as the narrative of women as innately peaceful, or as actors coerced into joining Daesh, revealing the importance of female empowerment in the group’s appeal.